Neuromarketing and consumer neuroscience - Reimann, Martin (Henry Stewart Talks, 2013)
Introduction, Advantages of consumer neuroscience, fMRI, Framework: classification of consumer neuroscience research, Stimuli, Measured processes, Conclusion, Future research